Electrooxidation of methanol and ethylene glycol mixture on platinum and palladium in alkaline medium - Li, Z.; Liang, Y.; Jiang, San Ping; Shan, X.; Lin, M.; Xu, C. (Wiley - V C H Verlag GmbH & Co. KGaA, 2012)
The performance of mixture of methanol and ethylene glycol (EG) oxidation has been studied on both Pt and Pd electrodes in alkaline medium. The activity of EG oxidation is better than that of methanol oxidation and the stability of EG oxidation is better than that of methanol and ethanol oxidation on the Pd electrode. The onset potential for ethanol oxidation is more negative 200 mV than that of EG, however the stability of EG oxidation on the Pd electrode is better than that of ethanol oxidation. The performance of methanol oxidation improves pronouncedly by adding a small amount of EG on both Pt and Pd electrodes. The onset potential and peak potential of mixture of methanol and EG oxidation are close to or more negative than that of sole methanol and EG oxidation on the Pd electrode. The mixture of methanol and EG is more easily to be electrochemically oxidized and gives a better performance than sole methanol and EG on the Pd electrode. The results show that the mixture of methanol and EG is a promising candidate as fuel in direct alcohol fuel cells.